KETAHANAN LIMA JENIS KAYU TERHADAP SERANGAN DELAPAN JENIS JAMUR PELAPUK - Sihati Suprapti; Esti Rini Satiti; Lisna Efiyanti; Djarwanto (Jurnal Penelitian Hasil Hutan, 2025)
Lesser-known wood originating from rain-forests is an alternative raw material for the national timber industry. Optimizing this wood group’s utilisation requires information on its resistance to the decaying fungus attack of each wood species used. This research is studying the resistance of five wood species from West Kalimantan, and the rust test was carried out on the metal embedded in heartwood and exposed to fungus using the Kolle-flask method. NaOH’s wood-solubility analysis referred to ASTM D-1110-84’s Standard. Results revealed that Albizia sp. and Syzygium sp. belonged to resistant woods (class II); Santiria sp. and Lithocarpus ewyckii belonged to moderately-resistant (class III); while Xanthophyllum excelsum belonged to not-resistant (class IV). The greatest weight loss occurred at sapwood of Xanthophyllum excelsum being exposed to Pycnoporus sanguineus. Average weight loss at heartwood (with class II) was lower than that at sapwood (class III). The greatest weight loss of woods embedded by screws occurred at screwed Syzygium sp. then exposed to Polyporus sp. The average weight loss of screwed woods was greater than that of unscrewed woods. Meanwhile, the highest weight loss of screws occurred at Xanthophyllum excelsum, then at Syzygium sp., exposed to Polyporus arcularius. The greatest weight of screw-rust powder was achieved at Syzygium sp. exposed to Polyporus arcularius. Five fungi species exhibited moderate capability, while three species afforded low capability in decaying woods. The effect of decaying fungi on corroding screws was entirely low.